Spatiotemporal and kinematic gait changes in flexible flatfoot: a systematic review and meta-analysis - Seyed-Alihossein Nourbakhsh; Rahman Sheikhhoseini; Hashem Piri; Fateme Soltani; Ebrahim Ebrahimi (Journal of Orthopaedic Surgery and Research)
Abstract Objectives Foot postural alignment is linked to changes in gait patterns. This review aimed to compare spatiotemporal and kinematic parameters of the lower extremities in individuals with and without flexible flatfoot. Methods Under PRISMA guidelines, a systematic review and meta-analysis were conducted by searching PubMed, Scopus, Web of Science, and Google Scholar databases for original and peer-reviewed articles with selected keywords from inception to November 2024. The quality of the included studies was assessed using the Joanna Briggs Institute checklist. Statistical analysis was conducted with Comprehensive Meta-Analysis software version 3. To evaluate data heterogeneity, the Q-test and I² statistic were applied. Egger’s test was used to assess publication bias. Results After searching the mentioned databases, 5309 articles were found. Finally, sixteen articles were included in the current review. A significant difference was found between the two groups in ankle inversion (effect size; 0.291, 95% CI = 0.053_0.053, P = 0.017), eversion (effect size; -0.568, 95% CI= -0.784_-0.352, P = 0.001), and hip flexion (effect size; -0.348, 95% CI= -0.576_-0.120, P = 0.003). Also, stride length (effect size; 0.658, 95% CI = 0.184_1.133, P = 0.007) and gait speed (effect size; 0.447, 95% CI = 0.120_0.774, P = 0.007) significantly differed between the two groups. Conclusion This study indicated that subjects with flatfoot exhibited alterations in the inversion, eversion, hip flexion, stride length, and walking speed compared to neutral foot participants and demonstrated a distinct gait pattern throughout the entire gait cycle. Health specialists are advised to consider these findings when prescribing prevention and rehabilitation programs for musculoskeletal deformities in individuals with flexible flatfoot.